Dihydrosphingosine driven enrichment of sphingolipids attenuates TGFβ induced collagen synthesis in cardiac fibroblasts. (August 2021) - Magaye, Ruth R.; Savira, Feby; Xiong, Xin; Huynh, Kevin; Meikle, Peter J.; Reid, Christopher; Flynn, Bernard L.; Kaye, David; Liew, Danny; Wang, Bing H.
Graphical abstract: Highlights: Increasing sphingolipid metabolism in cardiac fibroblasts inhibited TGFβ mediated collagen synthesis. Dihydrosphingosine inhibits collagen synthesis in cardiac fibroblasts through substrate-enzyme-receptor interaction. Dihydrosphingosine suppresses TGFβ/Smad and Akt signalling in cardiac fibroblasts. Abstract: The sphingolipid de novo synthesis pathway, encompassing the sphingolipids, the enzymes and the cell membrane receptors, are being investigated for their role in diseases and as potential therapeutic targets. The intermediate sphingolipids such as dihydrosphingosine (dhSph) and sphingosine (Sph) have not been investigated due to them being thought of as precursors to other more active lipids such as ceramide (Cer) and sphingosine 1 phosphate (S1P). Here we investigated their effects in terms of collagen synthesis in primary rat neonatal cardiac fibroblasts (NCFs). Our results in NCFs showed that both dhSph and Sph did not induce collagen synthesis, whilst dhSph reduced collagen synthesis induced by transforming growth factor β (TGFβ). The mechanisms of these inhibitory effects were associated with the increased activation of the de novo synthesis pathway that led to increased dihydrosphingosine 1 phosphate (dhS1P). Subsequently, through a negative feedback mechanism that may involve substrate-enzyme receptor interactions, S1P receptor 1 expression (S1PR1) was reduced.